New evidence on the effects of EU regional policy - Julia Bachtrögler; Mathias Dolls; Carla Krolage; Paul Schüle; Hannes Taubenböck; Matthias Weigand (EconPol Forum, 2024)
We present a novel approach to assess the effect of EU cohesion policy on economic activity. Project-level data on EU funding is combined with nighttime light emissions data. Higher EU funding is associated with increased economic activity at the municipal level. Remote sensing data can provide an effective way to model local economic development in Europe. Improved access to data on EU-funded projects would enhance transparency of EU regional funding.
Keywords: 330